Sodium–glucose Cotransporter 2 Inhibitors in Heart Failure: Potential Mechanisms of Action, Adverse Effects and Future Developments - Juan Tamargo (European Cardiology Review)
Heart failure is a common complication in patients with diabetes, and people with both conditions present a worse prognosis. Sodium– glucose cotransporter 2 inhibitors (SGLT2Is) increase urinary glucose excretion, improving glycaemic control. In type 2 diabetes (T2D), some SGLT2Is reduce major cardiovascular events, heart failure hospitalisations and worsening of kidney function independent of glycaemic control. Multiple mechanisms (haemodynamic, metabolic, hormonal and direct cardiac/renal effects) have been proposed to explain these cardiorenal benefits. SGLT2Is are generally well tolerated, but can produce rare serious adverse effects, and the benefit/risk ratio differs between SGLT2Is. This article analyses the mechanisms underlying the cardiorenal benefits and adverse effects of SGLT2Is in patients with T2D and heart failure and outlines some questions to be answered in the near future.